Heat Analysis in Friction Stir Welding Using Finite Element Method / Mohd Saiful Bahari... [et al.] - Bahari, Mohd Saiful; Jaffarullah, M. Shamil; Mohamed, Zulkifli; ., Armansyah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Heat is a key factor in friction stir welding (FSW) due to its capability to plasticize two stationary material (workpieces) in joining. The required heat energy is generated in such away by mechanical friction between rotating, traveling tool and workpieces itself. In this work the study which focused on the heat generation in FSW is done by using Finite Element Analysis software i.e. Altair HyperWorks. The generated and distributed heat across the workpieces of a 6mm thick Aluminium alloy 6061 during FSW is observed in this study. The objective of this study is to characterisize of the heat generation during FSW with respect to the welding parameters i.e. rotational and travel speed of the tool. In the analysis, a three dimensional symmetrical model was used to predict the generated and distributed heat by using the finite element method. Heat analysis and measurement during welding is carried out numerically and experimentally for validation. From the analysis and measurement is concluded that the maximum temperature gradients in longitudinal and lateral directions are located just beyond the shoulder edge. It can be seen that the heat flux is higher for higher tool rotation than the lower tool rotation. Both are set at constant travel speed. The maximum heat is proportional to the rotational speed. It is occured due to high frictional forces between the rotating tool and workpiece and increasing the heat generation around the tool. This study provided better insight about generated and distributed heat during FSW as a result of process parameters which can be used as reference to produced good quality of welding with less experiment.